Irish intellect, and its geographical distribution - Flinn, D. Edgar (Statistical and Social Inquiry Society of Ireland, 1889)
It is difficult in a paper of this nature to estimate who shall be deemed worthy of being included in a list of those who have contributed to Ireland's roll of fame; and I have undertaken the task of making an analysis in this direction with some hesitation, thoroughly appreciating the difficulties that attach to it, and feeling that to draw a hard and fast line as to who might, or who might not be considered to be a person of eminence, would be arbitrary and presumptive. Yet taking such books as Men of the Time, Celebrities of the Century, Men of the Reign, The Compendium of Irish Biography, The Cabinet of Irish Literature, as a guide as to who would be considered a person of eminence, or of distinguished intellect, and adding the names of those who, although not adjudged worthy of a place in these lists, are yet eminent, and of considerable reputation, we find the number to be 215.
Read 22nd January, 1889
Keywords: Famous Irishmen; Eminence; 314.15